Generación distribuida en alimentadores radiales - Rojas Vivanco, Luis Gabriel (2022)
This study analyzes the entry effects of 1 MW photovoltaic solar power plant in Alamor primary feeder. This power plant has been designed to be placed at Mangahurquillo neighborhood, in Puyango canton of Loja province. To develop this study, it was necessary to analyze the feeder current state to determine the network voltage levels, power flows, protections existing, conductor’s configuration and their size. The sizing of 1 MW solar plant was carried out based on the available information about solar resource in this area. The simulation of the solar plant entry, allowed us to contrast the new network advantages and drawbacks; concluding that, the income of distributed generation in long radial feeders with loads at their ends, improves the circuit furthest points voltage levels, as well as the quality of power quality throughout the feeder. Keywords: Distributed generation, solar energy, voltage level, radial feeder.